Unlocking the Potential of Browser- Based Scientific Data Analysis: A 20-Year Journey of Expertise - Luc Patiny (CHIMIA)
The browser has become an indispensable tool for a variety of everyday tasks, yet its potential in scientific data processing remains underexplored and is often perceived as slow. This paper presents four examples of advanced web applications that we have developed during the last 20 years and demonstrates the browser’s ability to compete with traditionally installed software. These applications were made possible through the development of over 100 open-source libraries, extending the FAIR (Findable, Accessible, Interoperable, and Reusable) principles to include not only data but also software.